Comparison of CpG islands in Genomes with Different Evolutionary Lineage - Kaur, Mehakpreet (My University, 2022)
The eukaryotic genome is said to be the most complex genome since it contains some of the most complicated modification mechanisms. Complexity has risen over time as a result of evolution and adaptation. The features of specific DNA segments are altered by several mechanisms and mutations, leading to evolution. DNA methylation followed by spontaneous deamination is one of the most important epigenetic modifications that distinguish certain regions known as CpG islands (CGI) from the rest of the genome. The DNA regions known as CpG islands have several unique qualities and properties that make them structurally as well as functionally important. Five genes were randomly selected for this study's assessment of CpG islands with regard to their higher eukaryotic species. The CGI and non-CGI sequences of these genes were identified and analysed for six different vertebrates. Based on CGI characteristics, the sequences were compared by constructing dendrograms. Comparison of dendrograms with phylogenetic trees showed poor overlap. The CGI sequences were compared based on their length, CG gaps, CG obs/exp and GC percentage. Some genes, like the Sox4 gene display very long CGIs and shortest CG gaps among all the genes studied in this work. It was observed that there is an inverse correlation between the length of CGIs and the gaps between the neighbouring CGs.
Keywords: DNA methylation; deamination; CGI sequences; non-CGI sequences; CG gaps; CG obs/exp; GC percentage